Sex-based differences in track running distances of 100, 200, 400, 800, and 1500m in the 8 and under and 9-10-year-old age groups - Brown, G. A.; Shaw, B. S.; Shaw, I. (European Journal of Sport Science, 2024)
There are contradictory claims regarding sex-based differences in athletic performance before puberty, but there has been minimal evaluation of sex-based differences in competitive running performance before puberty. The purpose of this project was to determine if there are prepubertal sex-based differences in track running performance. Finalist times from the USA Track and Field National Youth Outdoor Championships and National Junior Olympic Championships during the years 2016-2023 for running distances of 100, 200, 400, 800, and 1500m in the 8 and under and 9-10-year-old age groups were analyzed for sex-based differences. In the 8 and under age group, the males were, on average, faster (p = 0.000, Hedges' g = 0.632-0.834) than females by 4.0% in the distance of 100m, 4.7% in 200m, 5.3% in 400m, 6.7% in 800m, and 6.1% in 1500m. In the 9-10-year-old age group, the males were, on average, faster (p = 0.000, Hedges' g = 0.584-1.089) than females by 2.9% in the distance of 100m, 4.6% in 200m, 4.0% in 400m, 4.0% in 800m, and 5.9% in 1500m. In each distance and age group between 2016 and 2023, the individual fastest male was faster than the individual fastest female by 3.7 ± 2.3%. The present data indicate that, in elite competition, males in the 8 and under and 9-10-year-old age groups typically run faster than females of the same age by 2.9%-6.7% for running distances of 100, 200, 400, 800, and 1500m. These findings are of particular importance as government agencies and sports organizations consider policies regarding single sex sports competition for youth.